Kidney injury molecule‐1: More than just an injury marker of tubular epithelial cells?1. Issue 5 (28th January 2013) - Lim, Ai Ing; Tang, Sydney C.W.; Lai, Kar Neng; Leung, Joseph C.K.
Abstract Regardless of the original causes and etiology, the progression to renal function declines follows a final common pathway associated with tubulointerstitial injury, in which the proximal tubular epithelial cells (PTEC) are instrumental. Kidney injury molecule‐1 (KIM‐1) is an emerging biomarker, and its expression and release are induced in PTEC upon injury. KIM‐1 plays the role as a double‐edged sword and implicates in the process of kidney injury and healing. Expression of KIM‐1 is also associated with tubulointerstitial inflammation and fibrosis. More importantly, KIM‐1 expressing PTEC play the role as the residential phagocytes, contribute to the removal of apoptotic cells and facilitate the regeneration of injured tubules. The precise mechanism of KIM‐1 and its sheded ectodomain on restoration of tubular integrity after injury is not fully understood. Other than PTEC, macrophages (Mø) also implicate in tubular repair. Understanding the crosstalk between Mø and the injured PTEC is essential for designing appropriate methods for controlling the sophisticated machinery in tubular regeneration and healing. This article will review the current findings of KIM‐1, beginning with its basic structure, utility as a biomarker, and possible functions, with focus on the role of KIM‐1 in regeneration and healing of injured PTEC. J. Cell. Physiol. © 2013 Wiley Periodicals, Inc.